2019
DOI: 10.3892/mmr.2019.10219
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA FER1L4 inhibits cell proliferation and metastasis through regulation of the PI3K/AKT signaling pathway in lung cancer cells

Abstract: Lung cancer is among the most common malignancies worldwide; however, the current understanding of its detailed mechanism remains limited. Long non-coding RNAs (lncRNAs) were previously identified to serve significant roles in tumorigenesis. The present study aimed to investigate the role of a novel lncRNA, Fer-1-like family member 4 (FER1L4), in lung tumorigenesis. In the present study, it was demonstrated that the expression level of FER1L4 was significantly decreased in clinical lung cancer tissues and in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…In humans, the long non-coding RNA Fer1L4 plays a role in signaling, controlling cell proliferation, migration and apoptosis. The results of the vast majority of the studies are consistent with a function of Fer1L4 as a tumor suppressor in multiple types of cancer [32,[66][67][68]160,161]. The exception is a report about the Fer1L4 possible role in glioma progression, where high expression of Fer1L4 was associated with a poor disease prognosis [162].…”
Section: Fer1l4-a Non-muscle Ferlin Long Non-coding Rnamentioning
confidence: 53%
See 2 more Smart Citations
“…In humans, the long non-coding RNA Fer1L4 plays a role in signaling, controlling cell proliferation, migration and apoptosis. The results of the vast majority of the studies are consistent with a function of Fer1L4 as a tumor suppressor in multiple types of cancer [32,[66][67][68]160,161]. The exception is a report about the Fer1L4 possible role in glioma progression, where high expression of Fer1L4 was associated with a poor disease prognosis [162].…”
Section: Fer1l4-a Non-muscle Ferlin Long Non-coding Rnamentioning
confidence: 53%
“…In zebrafish tissues otoferlins a and b transcripts were detected in the sensory hair cells of the inner ear, otoferlin a in the mid-brain and retinal ganglion cell layer, whereas otoferlin b was in the hair cells of the lateral line [26]. Initially, Fer1L4 long noncoding RNA was found to be selectively transcribed in human stomach tissue [33], however, later Fer1L4 was detected in multiple normal tissues surrounding malignant tumors [65][66][67][68]. Fer1L5 is produced in myotubes [69], pancreas and at lower levels in a few other human tissues [33].…”
Section: Tissue Distribution Of the Ferlinsmentioning
confidence: 99%
See 1 more Smart Citation
“…7a, b). The activity of PI3K/AKT pathway was critical for survival and proliferation of prostate cancer and tightly regulated by FER1L4 in several cancer types [30,31]. Interestingly, in PC-3 and DU145 cells, we also observed that FER1L4 overexpression decreased the phosphorylation of AKT protein which was reversed towards FBXW7 silencing ( Fig.…”
Section: Fer1l4 Suppresses Cell Proliferation and Induce Cell Apoptosmentioning
confidence: 61%
“…FER1L4, a novel LncRNA, was first identified that its down‐regulated expression in human gastric cancer . Gao et al also found that FER1L4 was down‐regulated in NSCLC in vivo and in vitro, and overexpression of FER1L4 could inhibit cell metastasis through regulating the PI3K/Akt signal pathway . Many studies indicated that the PI3K/Akt signalling was aberrantly activated in human malignancies and was associated with tumour metastasis and drug resistance …”
Section: Main Molecular Mechanism Of Lncrna To Regulate the Metastasimentioning
confidence: 99%